Perencanaan Ulang Drainase Perumahan Griya Jean Tiakar Balai Batimah, Kecamatan Payakumbuh Timur, Kota Payakumbuh - Ezi Juniza; Sutria Desman; Ridha Sari (Fakultas Teknik Sipil dan Perencanaan, 2025)
The population growth in Payakumbuh City, which reaches 6,79 % per year, increases the demand for housing and reduces green infiltration areas. This condition leads to waterlogging and decreases the performance of the existing drainage system in Griya Jean Tiakar Housing, East Payakumbuh District. This research aims to redesign the drainage system to effectively accommodate stormwater runoff and domestic wastewater. The theoretical framework is based on hydrology and hydraulics principles by Suripin (2010) and Triatmodjo (2008), as well as the drainage planning standards of SNI and the Directorate General of Human Settlements. The study applied a quantitative approach, including hydrological analysis, design flood discharge calculation using the rational method, and channel capacity analysis using Manning’s equation. Primary data were obtained from field observations of existing conditions, while secondary data included 10-year rainfall records from the Tanjung Pati station. The results show that the planned discharge is 0,0373 m3/s, with an optimal channel dimension of 0,45 m height and 0,45 m width. The redesigned channel can adequately accommodate runoff and domestic wastewater without causing flooding. Therefore, this drainage redesign is expected to improve the residential drainage performance and support sustainable urban environmental management.